Capgras Delusion in Posterior Cortical Atrophy–A Quantitative Multimodal Imaging Single Case Study - Schroeter, Matthias L.; Albrecht, Franziska; Ballarini, Tommaso; Leuthold, Dominique; Legler, Angela; Hartwig, Simone; Tiepolt, Solveig; Villringer, Arno (Frontiers in Aging Neuroscience, 2020)
Although Alzheimer’s disease presents homogeneous histopathology, it causes several clinical phenotypes depending on brain regions involved. Beside the most abundant memory variant several atypical variants exist. Among them posterior cortical atrophy (PCA) is associated with severe visuospatial / visuoperceptual deficits in the absence of significant primary ocular disease. Here, we report for the first time a case of Capgras delusion – a delusional misidentification syndrome, where patients think that familiar persons are replaced by identical ‘doubles’ or an impostor – in a patient with PCA. The 57-year-old female patient was diagnosed with PCA and developed Capgras delusion eight years after first symptoms. The patient did not recognize her husband, misidentified him as a stranger and perceived him as a threat. Such misidentifications did not happen for other persons. Events could be interrupted by reassuring the husband’s identity by the patient’s female friend or children. We applied in-depth multimodal neuroimaging phenotyping and used single-subject voxel-based morphometry to identify atrophy changes specifically related to the development of the Capgras delusion. The latter, based on structural T1 magnetic resonance imaging, revealed progressive gray matter volume decline in occipital and temporoparietal areas, involving more the right than the left hemisphere, especially at the beginning. Correspondingly, the right fusiform gyrus was already affected by atrophy at baseline, whereas the left fusiform gyrus became involved in the further disease course. At baseline, glucose hypometabolism as measured by positron emission tomography (PET) with F18-fluorodesoxyglucose (FDG-PET) was evident in the parietooccipital cortex, more pronounced right-sided, and in the right frontotemporal cortex. Amyloid accumulation as assessed by PET with F18-florbetaben was found in the gray matter of the neocortex indicating underlying Alzheimer’s disease. Appearance of the Capgras delusion was related to atrophy in the right posterior cingulate gyrus/precuneus, as well as right middle frontal gyrus/frontal eye field, supporting right frontal areas as particularly relevant for Capgras delusion. Atrophy in these regions respectively might affect the default mode and dorsal attention networks as shown by meta-analytical co-activation and resting state functional connectivity analyses. This case elucidates the brain-behavior relationship in PCA and Capgras delusion.